Incidental Cystic Lymphangioma of the Small Bowel Mesentery - Cupido, Brindley David (J Clin Imaging Sci, 2015)
Lymphangiomas are benign lesions of mesenchymal origin. Although more commonly encountered in the head and neck, intra-abdominal lymphangiomas are a rare entity that typically present as multiloculated intra-abdominal cystic lesions that are often incidentally discovered on imaging. This case report discusses such a case.